Analisa Pertumbuhan Ikan Nila Larasati (Oreochromis niloticus) Yang Dipelihara Pada KJA Wadaslintang Dengan Kepadatan Berbeda - Islami, Erma Yunita; Basuki, Fajar; Elfitasari, Tita (Journal of Aquaculture Management and Technology, 2013)
Tilapia (Oreochormis niloticus) is one type of potential to cultured intensive in floating net cage because tilapia (Oreochormis niloticus) have biological characteristic benefit. Cultured tilapia (Oreochormis niloticus) in floating net cage is a aquaculture technic the most of productive. The case that happen is densities to applied for cultured in floating net cage on Wadaslintang, Wonosobo not optimal.The purpose of study is to observe the effect of different stocking densities and to observe the best of stocking densities towards feed utilization eficiency (EPP), growt h (W, RGR) and Survival rate( SR) of tilapia cultivated in floating net cage. The method used in this research was experimental method. The material that used was tilapia seed size 10 ± 20 cm with average individual weight 40± 60 g. The research design used completely randomized design (CMD) with 3 treatment and 3replications. The treatment tested A ( stocking densities of 50 fish/m³), B (stocking densities of 75 fish/m³), and C (stocking densities of 100 fish/m³). The feed was given 3 times a day. The result shows that the giving of different densities tilapia gives significant effect (P< 0,05) to the feed utilization eficiency (EPP),growth(W, RGR) and not gives significant (P>0,05) efect to Survival rate(SR).